2001
DOI: 10.1562/0031-8655(2001)074<0465:icfrct>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid Compounds from Red Clover (Trifolium pratense) Protect from Inflammation and Immune Suppression Induced by UV Radiation¶

Abstract: Isoflavones derived from many edible plants have been reported to possess significant antioxidant, estrogenic and tyrosine kinase inhibitory activity. Genistein has been found previously to provide protection from oxidative damage induced by UV radiation both in vitro and following dietary administration. We have therefore examined the potential of a number of isoflavones from red clover (Trifolium pratense) and some metabolically related compounds to offer protection from UV irradiation in hairless mice by to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 42 publications
(44 reference statements)
6
82
0
8
Order By: Relevance
“…Studies have shown that topically applied isoflavones and their metabolites may offer protection from UV-induced inflammation and immunosuppression [191]. The topical administration may also be a suitable route for soy isoflavones to obtain systemic bioavailability because of their rapid clearance from the plasma [192].…”
Section: Development Of Topical Formulations Containing Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that topically applied isoflavones and their metabolites may offer protection from UV-induced inflammation and immunosuppression [191]. The topical administration may also be a suitable route for soy isoflavones to obtain systemic bioavailability because of their rapid clearance from the plasma [192].…”
Section: Development Of Topical Formulations Containing Flavonoidsmentioning
confidence: 99%
“…Studies that have focused on equol ([S]-4 0 ,7-dihydroxyisoflavane) because it was shown that its contribution to the protection against solar-simulated UVR-induced erythemal-associated edema and immunosuppression [190] showed a potential role in the prevention of human skin cancer [190] by acting as a sunscreen and, thus, inhibiting DNA photodamage [191] when topically applied as a lotion.…”
Section: Development Of Topical Formulations Containing Flavonoidsmentioning
confidence: 99%
“…Consistent with this observation, it was found that topical application to humans of an equol-related synthetic isoflavonoid, NV-07␣, also protected against the UV radiation-induced suppression of the elicited Mantoux reaction (2). In mice it was shown that the immunoprotective mechanism of topically applied equol involved inactivation of the downstream actions of cis-urocanic acid, a major UV-induced immunosuppressive photoproduct produced in the skin (1). Because chronic photoimmune suppression is a prerequisite for the promotion of UV radiation-initiated tumors (3), and because topically applied equol was also demonstrated to have antiphotocarcinogenic properties in mice (4), the photoprotective effects of equol offer the opportunity to identify critical pathways linking the UV-induced immune defect with the development of skin cancer.…”
mentioning
confidence: 99%
“…Although many groups have demonstrated the beneficial effects of biochanin A, including an anti-proliferation effect on squamous cell carcinoma [41], anti-inflammatory, immune suppressive [42], and LDL cholesterol-lowering effects [43], the direct mechanisms of action of biochanin A are not fully understood. Several proteins and signaling pathways have been suggested to mediate the mechanism of biochanin A's actions.…”
Section: Discussionmentioning
confidence: 99%